2002
DOI: 10.1073/pnas.052703699
|View full text |Cite
|
Sign up to set email alerts
|

Surface-exposed positions in the transmembrane helices of the lactose permease of Escherichia coli determined by intermolecular thiol cross-linking

Abstract: bioenergetics ͉ transport ͉ membrane protein ͉ structure T he lactose permease of Escherichia coli (LacY) is a paradigm for membrane transport proteins that couple free energy stored in electrochemical ion gradients into solute concentration gradients (1-4). Thus, LacY catalyzes the coupled stoichiometric translocation of galactosides and H ϩ (lactose͞H ϩ symport), by using the free energy released from the downhill translocation of H ϩ to drive galactoside accumulation and vice versa. The protein has been sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 49 publications
2
41
0
2
Order By: Relevance
“…The hydrophilic cavity is lined with helices I, II, IV, and V of the N-terminal domain and helices VII, VIII, X, and XI of the C-terminal domain. Helices III, VI, IX, and XII are embedded largely in the bilayer and not exposed to solvent, as suggested by Guan et al (31).…”
Section: Tertiary Structurementioning
confidence: 62%
See 1 more Smart Citation
“…The hydrophilic cavity is lined with helices I, II, IV, and V of the N-terminal domain and helices VII, VIII, X, and XI of the C-terminal domain. Helices III, VI, IX, and XII are embedded largely in the bilayer and not exposed to solvent, as suggested by Guan et al (31).…”
Section: Tertiary Structurementioning
confidence: 62%
“…Finally, single-Cys replacement mutants in the transmembrane helices or loops of LacY dimerize in a stochastic manner (18,31,99). Moreover, the asymmetric unit of the LacY crystal is composed of an artificial dimer with two molecules oriented in opposite directions (2).…”
Section: Lacy Is Functional As a Monomermentioning
confidence: 99%
“…It has been reported that cross-linking easily occurs in the monomeric LacY, giving rise to an apparent dimer. Equivalent temperature experiments resulted in a reduction of the LacY dimer band by Ͼ90% (22). Fig.…”
Section: Dimerization Is a General Property Of Ktrb Membranementioning
confidence: 86%
“…4D). The low temperature was set below a phase transition of the E. coli lipid bilayer so that lateral diffusion within the membrane was decreased, resulting in a reduction of collisions between dimers (22,26). It has been reported that cross-linking easily occurs in the monomeric LacY, giving rise to an apparent dimer.…”
Section: Dimerization Is a General Property Of Ktrb Membranementioning
confidence: 99%
“…1). LacY has been solubilized from the membrane, purified to homogeneity in a highly functional state (2), and is structurally (3,4), as well as functionally (5), a monomer.…”
mentioning
confidence: 99%